The Moderating Role of Social Media Marketing and the Effect of Price Perception and Brand Identity on Purchase Intention Through Perceived Value as a Mediator Variable at Carina Florist in Surabaya City - Azarine Nahdah Amelia; Abdul Halik; Endah Budiarti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study aims to analyse the effect of perceived price and brand identity on purchase intention with perceived value as a mediating variable and social media marketing as a moderating variable at Carina Florist in Surabaya City. A quantitative approach with an explanatory type of research was used in this study. Data collection was carried out through online questionnaires to the people of Surabaya City using probability sampling techniques. Data analysis using the Partial Least Square (PLS) method with SmartPLS software. The results showed that perceived price and brand identity have a significant influence on perceived value. In addition, perceived price and perceived value also have a significant effect on purchase intention. However, brand identity has no significant effect on purchase intention, and social media marketing does not moderate the relationship between perceived value and purchase intention. The study's conclusions highlight the importance of pricing strategies, perceived value reinforcement, and social media marketing optimisation to increase purchase intentions at Carina Florist.